2019
DOI: 10.1155/2019/3457846
|View full text |Cite
|
Sign up to set email alerts
|

Indicaxanthin from Opuntia ficus indica (L. Mill) Inhibits Oxidized LDL-Mediated Human Endothelial Cell Dysfunction through Inhibition of NF-κB Activation

Abstract: Oxidized low-density lipoproteins (oxLDL) play a pivotal role in the etiopathogenesis of atherosclerosis through the activation of inflammatory signaling events eventually leading to endothelial dysfunction and senescence. In the present work, we investigated the effects of indicaxanthin, a bioavailable, redox-modulating phytochemical from Opuntia ficus indica fruits, with anti-inflammatory activity, against oxLDL-induced endothelial dysfunction. Human umbilical vein cord cells (HUVEC) were stimulated with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Their inhibition could be, therefore, crucial to explain the beneficial effects exerted by the pigment against the HFD-induced macrophage infiltration, activation and IR development. The ability of indicaxanthin to inhibit NF-κB signalling in this HFD model is consistent with our previous observations in other inflammatory-related models, where the yellow betalain was shown to counteract inflammation and tumour progression via NF-κB inhibition, both in vivo and in vitro [ 26 , 27 , 28 , 29 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Their inhibition could be, therefore, crucial to explain the beneficial effects exerted by the pigment against the HFD-induced macrophage infiltration, activation and IR development. The ability of indicaxanthin to inhibit NF-κB signalling in this HFD model is consistent with our previous observations in other inflammatory-related models, where the yellow betalain was shown to counteract inflammation and tumour progression via NF-κB inhibition, both in vivo and in vitro [ 26 , 27 , 28 , 29 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of biochemical mechanisms, disruption of glucose homeostasis can be envisaged as the result of a self-feeding cycle between systemic, chronic inflammation and oxidative stress, initiated by excess nutrient consumption. Along these lines, one potential explanation for the beneficial effects of indicaxanthin supplementation on insulin sensitivity may lie in its anti-inflammatory properties [ 25 , 26 , 28 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes migrate to the subendothelial space and become the activated macrophages, which uptake ox-LDL to become foam cells, and the atherosclerotic plaque is thus formed [38]. The expression of the endothelial adhesion molecules ICAM and VCAM is controlled by NF-κB [39]. Considering that the NF-κB pathway is activated by silencing NORAD, we further examined the changes of ICAM and VCAM levels.…”
Section: Agingmentioning
confidence: 99%
“…We observed that the plasma hydroperoxides significantly increased after testing, however the increase was smaller in the group supplemented with OFI than placebo group, thus suggesting that OFI juice was able to limit the formation of ROS and increase antioxidant capacity. Our previous study [ 16 ] and the known activity of indicaxanthin as an antioxidant and modulator of the redox balance of cells under a number of pathophysiological conditions [ 34 , 35 ] suggest a role for this phytochemical in the observed effect. With respect to OFI supplementation, Khouloud et al 18 following an intermittent yo-yo maximal aerobic effort test, not only described a decrease of oxidative stress following OFI supplementation, but also a reduction in the total and LDL cholesterol.…”
Section: Discussionmentioning
confidence: 99%